IMPROVING THE METHODOLOGY OF SPIRITUAL EDUCATION THROUGH ARTIFICIAL INTELLIGENCE TOOLS - Khojaeva Gulshoda Jalilovna (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2026)
The rapid integration of artificial intelligence into educational systems has transformed the methods, content, and structure of teaching and learning processes across the world. In contemporary education, spiritual education occupies a central role in shaping morally responsible, socially active, and intellectually mature individuals. However, traditional approaches to spiritual and moral upbringing often fail to fully engage digital-native learners who are deeply connected to technological environments. This study examines the possibilities of improving the methodology of spiritual education through artificial intelligence tools in modern educational institutions. The research analyzes how AI-based platforms, adaptive learning systems, virtual assistants, intelligent tutoring systems, natural language processing technologies, and personalized educational environments can contribute to the development of students’ moral values, ethical awareness, national identity, empathy, tolerance, and reflective thinking. The article also explores the pedagogical, psychological, and technological foundations of integrating AI into spiritual education.